2009
DOI: 10.1080/17538150902779204
|View full text |Cite
|
Sign up to set email alerts
|

User information seeking behaviour: Perceptions and reality. An evaluation of the WHO Labresources Internet portal

Abstract: Evaluation on Internet portals is a key component of any online resource development. Understanding user information seeking behaviour and user perceived behaviour is essential to obtain the full picture of user needs, online activities and draw lessons to improve the design of Internet portals to better meet user expectations. This article discusses the evaluation of a WHO Internet portal: the Labresources website. The evaluation investigates user satisfaction with the resource, usability, demographic informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Further, as the users were self-selected it is likely that these volunteers were more enthusiastic in using technology in their clinical practise and therefore present a certain bias to the study. As we relied on self-reported attitudes and behaviour, there is a known issue with a discrepancy between user selfperceived behaviour and real behaviour [32,33], however, without expensive resource demanding observational studies self-reporting is the only way to collect data from user.…”
Section: Limitations Of This Approachmentioning
confidence: 99%
“…Further, as the users were self-selected it is likely that these volunteers were more enthusiastic in using technology in their clinical practise and therefore present a certain bias to the study. As we relied on self-reported attitudes and behaviour, there is a known issue with a discrepancy between user selfperceived behaviour and real behaviour [32,33], however, without expensive resource demanding observational studies self-reporting is the only way to collect data from user.…”
Section: Limitations Of This Approachmentioning
confidence: 99%
“…The need for more in-depth evaluation using multiple data collection methods, in addition to weblogs, was demonstrated by authors who illustrated a disproportion between website developers' aims and users' needs, and also between perceived and actual user behaviour. These were shown on an evaluation of NeLI DL [10] and on an evaluation of a WHO portal, called "Labresources" [11], for microbiologists in developing world.…”
Section: Internal Nric Site Search Abstract In 2008mentioning
confidence: 99%
“…Madle et al recently carried out a survey of the WHO Labresources portal involving twenty-one participants. Their results showed that browsing via the navigation menu was more popular than using search box [12]. However, since the invited participants were all public health professionals, they were expectedly more familiar with medical terminology and categorization of medical topics.…”
Section: Introductionmentioning
confidence: 99%